2020
DOI: 10.1371/journal.pone.0239155
|View full text |Cite
|
Sign up to set email alerts
|

A 2-year longitudinal follow-up of performance characteristics in Chinese male elite youth athletes from swimming and racket sports

Abstract: Training in elite sport aims at the optimization of the athletic performance, and to control the athletes'progress in physiological, anthropometrical and motor performance prerequisites. However, in most sports, the value of longitudinal testing is unclear. This study evaluates the longitudinal development and the influence of intense training over 2-years on specific physiological performance prerequisites, as well as certain body dimensions and motor abilities in elite youth athletes. Recruited between 11-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Norway Quantitative non-randomised 1 1 1 1 1 5 Moseid et al 2019b [58] Norway Quantitative non-randomised 1 1 1 1 1 5 Mudrak and Zabrodska 2014 [43] Czech Republic Qualitative 1 1 1 1 1 5 Perez-Rivases et al 2020 [48] Spain Quantitative non-randomised 1 1 1 1 1 5 Rasyid et al 2020 [73] Malaysia Quantitative descriptive 1 1 1 1 1 5 Romar 2012 [44] Finland Quantitative descriptive 0 1 0 1 0 2 Ronkainen et al 2020 [59] Finland Qualitative 1 1 1 1 1 5 Ronkainen and Ryba 2018 [66] Finland Qualitative 1 1 1 1 1 5 Rosendahl et al 2009 [60] Germany Quantitative descriptive 1 1 1 1 1 5 Ryba et al 2017 [36] Finland Qualitative 1 1 1 1 1 5 Sandström et al 2012 [ 61] Sweden Quantitative non-randomised 1 1 1 1 1 5 Skrubbeltrang et al 2020 [45] Denmark Quantitative descriptive 1 1 0 1 0 3 Skrubbeltrang et al 2016 [67] Denmark Qualitative 1 1 1 1 1 5 Sorkkila et al 2017 [18] Finland Quantitative descriptive 1 1 1 1 1 5 Sorkkila et al 2018 [74] Finland Quantitative non-randomised 1 1 1 1 1 5 Sorkkila et al 2019 [75] Sweden Quantitative non-randomised 1 1 1 1 1 5 Stambulova et al 2015 [37] Sweden Mixed methods 1 1 1 1 1 5 Stenling et al 2015 [62] Sweden Quantitative descriptive 1 1 1 0 1 4 Stornaes et al 2019 [63] Norway Quantitative non-randomised 1 1 1 1 1 5 van Rens et al 2012 [49] Netherlands Quantitative non-randomised 1 0 1 1 0 3 Zhao et al 2020 [64] China Quantitative non-randomised 1 1 1 0 1 4…”
Section: Moseid Et Al 2019a [57]mentioning
confidence: 99%
“…Norway Quantitative non-randomised 1 1 1 1 1 5 Moseid et al 2019b [58] Norway Quantitative non-randomised 1 1 1 1 1 5 Mudrak and Zabrodska 2014 [43] Czech Republic Qualitative 1 1 1 1 1 5 Perez-Rivases et al 2020 [48] Spain Quantitative non-randomised 1 1 1 1 1 5 Rasyid et al 2020 [73] Malaysia Quantitative descriptive 1 1 1 1 1 5 Romar 2012 [44] Finland Quantitative descriptive 0 1 0 1 0 2 Ronkainen et al 2020 [59] Finland Qualitative 1 1 1 1 1 5 Ronkainen and Ryba 2018 [66] Finland Qualitative 1 1 1 1 1 5 Rosendahl et al 2009 [60] Germany Quantitative descriptive 1 1 1 1 1 5 Ryba et al 2017 [36] Finland Qualitative 1 1 1 1 1 5 Sandström et al 2012 [ 61] Sweden Quantitative non-randomised 1 1 1 1 1 5 Skrubbeltrang et al 2020 [45] Denmark Quantitative descriptive 1 1 0 1 0 3 Skrubbeltrang et al 2016 [67] Denmark Qualitative 1 1 1 1 1 5 Sorkkila et al 2017 [18] Finland Quantitative descriptive 1 1 1 1 1 5 Sorkkila et al 2018 [74] Finland Quantitative non-randomised 1 1 1 1 1 5 Sorkkila et al 2019 [75] Sweden Quantitative non-randomised 1 1 1 1 1 5 Stambulova et al 2015 [37] Sweden Mixed methods 1 1 1 1 1 5 Stenling et al 2015 [62] Sweden Quantitative descriptive 1 1 1 0 1 4 Stornaes et al 2019 [63] Norway Quantitative non-randomised 1 1 1 1 1 5 van Rens et al 2012 [49] Netherlands Quantitative non-randomised 1 0 1 1 0 3 Zhao et al 2020 [64] China Quantitative non-randomised 1 1 1 0 1 4…”
Section: Moseid Et Al 2019a [57]mentioning
confidence: 99%
“…Six articles also reported a range of participant observations of three or more [ 34 , 36 , 47 , 51 , 65 , 67 ]. The remaining articles either confirmed that all participants were observed at all time points [ 13 , 28 , 30 , 33 , 35 , 46 , 56 , 58 , 59 , 64 , 66 ], or the number of participant observations was not stated [ 29 , 31 , 32 , 37 , 42 , 48 , 49 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies (33%) used complete case analysis [ 28 , 30 , 36 , 40 , 49 , 50 , 55 , 56 , 58 , 60 , 65 , 66 , 68 ]. Eight studies (20%) stated within the analysis justification that the method could accommodate missing values [ 35 , 38 , 39 , 44 , 45 , 47 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies comparing young swimmers and controls show that the former are taller and heavier and have broader shoulders [ 21 , 22 ]. Similar differences are found between boys with different swimming skills.…”
Section: Discussionmentioning
confidence: 99%